Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Pada Rumah Kopi +62 Jl. Raya Kalimulya Cilodong Depok - Agista Azzahra Ainunnisa; Ali Mubarok (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The purpose of this study was to find out whether price and promotion affect the purchasing decision at Rumah Kopi +62 in Jl. Raya Kalimulya Cilodong, South Depok, either partially or simultaneously. This research method uses quantitative research methods with an associative approach. The sample used in this study was a random sample, namely using a portion of the population totaling 100 respondents as a sample. Data collection techniques using questionnaires. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. Based on the results of SPSS version 26 data processing, there is an influence between price on purchasing decisions, the value of the regression equation Y = 11,897 + 0.903X1 means that it has a positive effect. The hypothesis test obtained is tcount > ttable or (11,343 > 1.664). Thus H0 is rejected H1 is accepted, this shows that there is a partially significant effect between price and purchasing decisions at Rumah Kopi +62 Cilodong, south Depok. While the promotion of purchasing decisions obtained the value of the regression equation Y = 12,421 + 0.882X2 which means it has a positive effect. The hypothesis test obtained tcount> ttable or (12,774 > 1.664). Thus, H0 is rejected and H2 is accepted, this shows that there is a partially significant influence between promotions on purchasing decisions at Rumah Kopi +62 Cilodong, south Depok. Then, the effect of price and promotion on purchasing decisions is obtained by the value of the regression equation Y = 9,464 + 0.364X1 + 0.598X2 which means it has a positive effect. The f test obtained fcount > ftable or (90,814 > 3.09). Thus, H0 is rejected and H3 is accepted, this shows that there is a positive and significant influence simultaneously between price and promotion on purchasing decisions at Rumah Kopi +62.